If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 5x = -16 + 2x Solving 17 + 5x = -16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 17 + 5x + -2x = -16 + 2x + -2x Combine like terms: 5x + -2x = 3x 17 + 3x = -16 + 2x + -2x Combine like terms: 2x + -2x = 0 17 + 3x = -16 + 0 17 + 3x = -16 Add '-17' to each side of the equation. 17 + -17 + 3x = -16 + -17 Combine like terms: 17 + -17 = 0 0 + 3x = -16 + -17 3x = -16 + -17 Combine like terms: -16 + -17 = -33 3x = -33 Divide each side by '3'. x = -11 Simplifying x = -11
| 2x^8-200=0 | | s+44=83 | | 5x^4+3x+(4-3x^4)*2=27 | | k+-28=-87 | | 8.2E+11= | | 8m+6k=20 | | 5x^4+3x+(4-3x)*2=27 | | 5x+5-13=12 | | 84=4(6)(3)+2(3)h | | x^2+9x+8=(x+g)(x+h) | | 0.2a=46-0.03a | | 5-x-7=9 | | 5x+88+2x+141=180 | | 3(x+5)+8x=11x-15 | | (2x-2)= | | y=n^2-8n+16 | | -2/3x+6=-2 | | 4a-5(7+7a)= | | 3x^2y-2xy^2+16xy=0 | | 2x-9=-4 | | 12x-5y=70 | | 1/2(8x-16)=6x+2-4x | | 25z^2-9z^4=0 | | (x+2)=(x-5)+7 | | 0.7x-6.2=0.1 | | 3w=32-5w | | 7(x+3)=4+3x | | 1+2n+3=4n-6 | | 26-x=8 | | (y)-8=32 | | 15x-2=180 | | 14x=35+7x |